Sociopolitical Determinants of Canada’s FIAP in Post-Conflict Recovery: Jordan, Myanmar, Nigeria. - Januari Pratama Nurratri Trisnaningtyas; Annisa Diah Pitaloka; Nadhea Khoirun Nabila; Azzahra Keyne Nabilla Radliyati (Indonesian Journal of Peace and Security Studies (IJPSS), 2025)
This study examines how sociopolitical factors shape the implementation of Canada’s Feminist International Assistance Policy (FIAP) in three partner countries—Jordan, Myanmar, and Nigeria in 2020-2024. Using a comparative qualitative approach grounded in the Most Similar Systems Design (MSSD), the research explores how varying political institutions, social structures, and governance conditions influence the translation of feminist foreign policy principles into practice. Findings reveal that while FIAP’s three core pillars, Rights, Resources, and Representation, are consistently implemented, their outcomes vary significantly across contexts. In Jordan, implementation has been relatively effective due to institutional stability and state–civil society collaboration. In contrast, Myanmar’s political instability following the 2021 military coup has constrained FIAP’s reach, forcing a shift toward localized and community-level empowerment initiatives. Meanwhile, Nigeria demonstrates a hybrid outcome, where grassroots engagement and strong civil society networks have driven progress in women’s economic participation and local governance, despite enduring structural inequalities. The study concludes that the effectiveness of FIAP depends not only on program design but also on the compatibility between feminist policy frameworks and the sociopolitical realities of recipient countries, highlighting the importance of contextual sensitivity in advancing global gender equality agendas.